MAXIMIZING TECHNOLOGY IN LANGUAGE TEACHING - Cecilia Titiek Mumiati (Soegijapranata Catholic University, 2002)
In this digital era. the computer has an increasingly important role in improving all aspects of life. Most people use the computer to make their task easier andfaster. Likewise. in language teaching. it has been widely used to enhance the teaching and learning process. Learners as well as teachers can take advalltage of . computers. Some of Ihe advantages are Ihe so-called Computer Enhanced Instruction. and the electronic mail. Computer Enhanced Instruction refers to language software and courseware that learners can use either independently or in-groups. Internet as one of the most amazing inventions in the 20